Nursing supervision and PPE compliance: The role of psychological safety - Supriyati, Endang; Abdurrouf, Muhammad; Sari, Dyah Wiji Puspita (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: The use of personal protective equipment (PPE) is one of the standard precautions in hospitals. The use of gloves aims to prevent cross-transmission of infection. Supervision serves as a management function in infection prevention and control by ensuring that glove use complies with established regulations. Purpose: To analyze the relationship between supervision and nurses’ compliance with glove use in the inpatient ward. Method: A quantitative design with a cross-sectional approach. The study sample consisted of 121 inpatient ward nurses at Kariadi Hospital, Semarang, selected using a total sampling technique. Data were collected using a questionnaire that had been tested for validity and reliability. Most nurses demonstrated compliance with glove use and received good levels of supervision. A significant relationship was found between supervision and the level of nurse compliance in using gloves. Results: The p-value was 0.002 (<0.05), indicating a moderate correlation strength with a positive correlation direction. Better supervision was associated with higher levels of nurse compliance in glove use. Conclusion: More structured and continuous supervision regarding glove-use compliance needs to be developed as an effort to improve service quality and enhance patient safety. Keywords: Compliance Level; Gloves; Nurses; Personal Protective Equipment; Supervision.